2021
DOI: 10.1242/dev.199780
|View full text |Cite
|
Sign up to set email alerts
|

Duplicated antagonistic EPF peptides optimize grass stomatal initiation

Abstract: Peptide signaling has emerged as a key component of plant growth and development, including stomatal patterning, which is critical for plant productivity and survival. Although exciting progress has been made in understanding EPIDERMAL PATTERNING FACTOR (EPF) signaling in Arabidopsis, the mechanisms by which EPF peptides control different stomatal patterns and morphologies in grasses is poorly understood. Here, by examining expression patterns, overexpression transgenics, and cross-species complementation, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Previous work has suggested the STOMAGEN paralog EPFL10 (LOC_Os08g41360) may function as a weak, positive regulator of stomatal development 28,29 , having arisen from a putative duplication event in the most recent common ancestor of the Poaceae species 27 . We examined evolutionary divergence of STOMAGEN and EPFL10 that may explain such functional differences.The two paralogs have accumulated divergent point mutations.…”
Section: Evolution and Regulation Of Stomagen And Epfl10 Suggests Fun...mentioning
confidence: 99%
See 1 more Smart Citation
“…Previous work has suggested the STOMAGEN paralog EPFL10 (LOC_Os08g41360) may function as a weak, positive regulator of stomatal development 28,29 , having arisen from a putative duplication event in the most recent common ancestor of the Poaceae species 27 . We examined evolutionary divergence of STOMAGEN and EPFL10 that may explain such functional differences.The two paralogs have accumulated divergent point mutations.…”
Section: Evolution and Regulation Of Stomagen And Epfl10 Suggests Fun...mentioning
confidence: 99%
“…Transgenic overexpression of rice STOMAGEN and its duplicate, previously named EPFL9-2, in A. thaliana revealed a shared, though attenuated, function of EPFL9-2 as a positive regulator of stomatal development when ectopically expressed 28 . Ectopic expression of Brachypodium distachyon and Triticum aestivum (wheat) STOMAGEN and STOMAGEN paralogs in A. thaliana resulted in similar stomatal density increases 29 . In contrast, overexpression of negative regulators of stomatal development reduced stomatal density.…”
Section: Introductionmentioning
confidence: 99%
“…Many core players guiding grass stomatal de- velopment were characterized (Abrash et al, 2018;Cartwright et al, 2009;Facette et al, 2015;Humphries et al, 2011;Jangra et al, 2021;Liu et al, 2009;Nunes et al, 2020;Raissig et al, 2017Raissig et al, , 2016Wang et al, 2019;Wu et al, 2019), whereas hair cell formation remains poorly explored (Torii, 2021). Few grass trichome initiation factors such as the transcription factors HAIRY LEAF 6 (HL6) (Fei et al, 2020;Sun et al, 2017)(Angeles-Shim et al, 2012Sun et al, 2017) and SQUAMOSA PROMOTER BINDING PROTEIN-LIKE 10/14/26 (SPL10/14/26) (Kong et al, 2021) , (Lan et al, 2019; were identified in rice and maize, but factors that affect morphogenesis and size remain mostly unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, the mechanisms that coordinate the formation and growth of stomata and trichomes remain highly unexplored. Many core players guiding grass stomatal development were characterized 2,3,18,[43][44][45][46][47][48][49][50] , whereas grass hair cell formation remains poorly explored 41 . Few grass trichome initiation factors such as the transcription factors HAIRY LEAF 6 (HL6) [51][52][53] and SQUAMOSA PROMOTER BINDING PROTEIN-LIKE 10/14/26 (SPL10/14/26) 5,54,55 were identified in rice and maize, but factors that affect morphogenesis and size remain mostly unknown.…”
Section: Discussionmentioning
confidence: 99%